PENGARUH AUDIT FEE, MASA KERJA AUDIT, ROTASI AUDIT, DAN KOMITE AUDIT TERHADAP KUALITAS AUDIT - Jessica Jessica; Erin Belinda; Meirike Lorencia; Silvi Tannitri; H. Adam Afiezan (Jurnal Akuntansi Trisakti, 2021)
The objective of this research is to analyse the effect of audit fees, audit working period, audit alternation and audit committee on audit quality in Indonesia Stock Exchange (IDX) listed manufacturing corporation during 2018-2020. Every influence factors is examined by measuring and calculating according to the reference: The audit quality is estimated by dummy variables by Big Four and Non Big Four KAP categories; The audit fee is calculated using the In (fee) formula with audit fee data taken from the professional fee account; The audit tenure is calculated by duration in years of KAP bond with clients; The audit rotation is measured using a dummy variable; The audit committee is measured based on the number of audit committees. This study uses secondary data and documentation methods for data collection as reference. With the purposive sampling method and research population of 193 manufacturing companies, 61 companies are eligible becoming samples according to following requirements: the corporation is recorded on the Indonesian stock exchange, the corporation presents audited reports, the corporation uses the rupiah currency in its reports and the corporation provides the required datasheet during 2018-2020. Procedure of this study is logistic regression to analyse the influence of these factors. This study outcome is about how the audit working period and the audit personel could bring positive impact on the audit quality, while the auditor alternation and the audit fee have no influence on the audit quality.